The association of chlorhexidine digluconate and calcium chloride to use as vehicle of a silicate calcium-based cement - Carmo Monteiro, Jardel Camilo do; Kuga, Milton Carlos [UNESP]; Faria, Gisele [UNESP]; Duarte, Marco Antonio Hungaro; Tanomaru-Filho, Mario [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Segalla, Jose Claudio Martins [UNESP] (Incessant Nature Science Publishers, 2015)
Objective: The purpose of this study was to evaluate the influence of the addition of 2% chlorhexidine digluconate (CHX) associated with 5% calcium chloride (CaCl2 ) on antimicrobial activity, setting time, pH and calcium release of gray mineral trioxide aggregate (GMTA). Materials and Methods: GMTA powder was mixed with water, 2% CHX alone or 2% CHX combined with 5% CaCl2 . Antimicrobial activity was determined against Enterococcus faecalis (ATCC 29212) strains by agar diffusion test. Data obtained were submitted to kruskal wallis tests. Analysis of the setting time was evaluated by American society for testing and materials C266-03 requirements. The pH and calcium release analysis were evaluated, in 24 h, 7, 14 and 28 days using pH meter equipment and atomic absorption spectrophotometer, respectively. Data obtained were analyzed by ANOVA, in 5% significance level. Results: Significant differences were seen (P < 0.01) among the zones of bacterial growth inhibition produced by 5% CaCl2 + 2% CHX combination against E. faecalis when compared with water (P < 0.05). Regarding the setting time, that combination had the shortest setting time (P < 0.05). All associations were alkaline and released calcium. No statistical difference was observed between the experimental groups at the different periods of analysis (P > 0.05). Conclusion: Combination of 5% CaCl2 + 2% CHX reduced the setting time and enhanced the antimicrobial activity of GMTA without changing the pH and calcium release.